2013
DOI: 10.1007/s11121-013-0402-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Smoking and Depressive Symptoms Among Adolescent Girls

Abstract: Adolescence is an important period for initiation of smoking and manifestation of depression, which are often comorbid. Researchers have examined associations between depressive symptoms and smoking to elucidate whether those with increased depressive symptoms smoke more to self-medicate, whether those who smoke experience increased subsequent depressive symptoms, or both. Collectively, there have been mixed findings; however, studies have been limited by a) cross-sectional or short-term longitudinal data, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
(62 reference statements)
2
14
0
Order By: Relevance
“…127 One study investigated the association of baseline anxiety with subsequent smoking heaviness and found no evidence of an association. 124 Eight studies investigated the association of heaviness of smoking with later depression, of which seven (88%) found evidence to support this association, 11,82,95,102,125,127,128 while one (13%) found no evidence of an association. 129 One study investigated the association of heaviness of smoking with later anxiety and found evidence to support this association.…”
Section: Resultsmentioning
confidence: 99%
“…127 One study investigated the association of baseline anxiety with subsequent smoking heaviness and found no evidence of an association. 124 Eight studies investigated the association of heaviness of smoking with later depression, of which seven (88%) found evidence to support this association, 11,82,95,102,125,127,128 while one (13%) found no evidence of an association. 129 One study investigated the association of heaviness of smoking with later anxiety and found evidence to support this association.…”
Section: Resultsmentioning
confidence: 99%
“…Depression and depressive symptoms are consistently observed in smoking adolescents compared to their non-smoking peers (Wu and Anthony, 1999 ; Goodman and Capitman, 2000 ; Albers and Biener, 2002 ; Jacobsen et al, 2007c ; Needham, 2007 ; Ilomäki et al, 2008 ; Audrain-Mcgovern et al, 2009 ; Morrell et al, 2010 ; Slomp et al, 2019 ). Most studies of this age group found smoking positively predicted the development of depression and depressive symptoms (Brown et al, 1996 ; Stein et al, 1996 ; Choi et al, 1997 ; Goodman and Capitman, 2000 ; Windle and Windle, 2001 ; Albers and Biener, 2002 ; Brook et al, 2002 , 2004 ; Galambos et al, 2004 ; Duncan and Rees, 2005 ; Rodriguez et al, 2005 ; Boden et al, 2010 ; Moon et al, 2010 ; Jamal et al, 2011 ; Beal et al, 2014 ; Gage et al, 2015 ), but not all findings have supported this association (Wang et al, 1996 ; Repetto et al, 2005 ; Clark et al, 2007 ; Munafò et al, 2008 ; Hu et al, 2011 ; Strong et al, 2014 ). Importantly, the relationship between smoking and depression in adolescence has been suggested to be bidirectional, such that baseline depression contributes to the risk for future smoking habits just as baseline smoking predicts depression (Brown et al, 1996 ; Windle and Windle, 2001 ; Galambos et al, 2004 ; Needham, 2007 ; Audrain-Mcgovern et al, 2009 ; Moon et al, 2010 ).…”
Section: Tobacco and E-cigarettesmentioning
confidence: 99%
“…Similarly, Clark, Ringwalt, & Shamblen (2011) investigated whether depressive symptoms predicted future smoking among middle school students and found that depressed mood while in 6 th grade predicted cigarette use in the 8 th grade. In contrast, Beal, Negriff, Dorn, Pabst, and Schulenberg (2014) explored the association in a sample of adolescents girls from ages 11 to 20 using latent dual change scores. They found that higher levels of smoking predicted an increase in depressive symptoms across the years.…”
Section: The Association Of Smoking and Depression In Adolescentsmentioning
confidence: 99%
“…The relationship between depression and smoking in adolescents is complex. The way the relationship has been studied varies based on distinct methodologies used, which is further complicated by a variety of distinct population characteristics that have been studied (e.g., younger vs. older adolescents, girls vs. boys, and clinical vs. non-clinical samples) (Beal et al, 2014;Wilkinson et al, 2016). Researchers have been investigating the mechanisms and the nuances of this association among adults and adolescents.…”
Section: The Relationship Between Smoking and Depression In Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation